Prognostic values of serum bilirubin at 7th day post-Kasai for survival with native livers in patients with biliary atresia - Sinobol Chusilp (2018)
© 2016, Springer-Verlag Berlin Heidelberg. Background: Biliary atresia (BA) is a serious liver disease with uncertain prognosis. The objective of this study was to investigate prognostic values of the >20 % decrease in serum total bilirubin (TB) at 7th day post-op regarding early outcome and 5-year survival with native liver in BA. Methods: Biliary atresia patients undergoing Kasai operation between 2000 and 2014 were reviewed. The ratio of serum TB at 7th day post-op to pre-op TB levels (TB7/TB0) was calculated for every patient. TB7/TB0 ratio of <0.8 indicated the >20 % decrease in serum TB. At 6th month following Kasai operation, outcome of BA patients were categorized into good outcome (TB < 2 mg % or clinically jaundice free) and poor outcome (TB > 2 mg % or clinically jaundice). For outcome analysis, logistic regression was used. For survival analysis, Cox regression was applied. Results: There were 133 BA patients (M:F = 68:65) undergoing Kasai operation. Median age at surgery was 79 days. BA patients with TB7/TB0 ratio of <0.8 were found in 38 %. Outcome at 6-month post-op could be evaluated in 126 patients (good: poor = 68:58). The 1-, 3- and 5-year survival rates with native livers were 85, 70 and 65 %, respectively. The median overall survival with native livers was 164 months. Median follow-up time was 87 months. Logistic regression showed that gender and age at operation were not significant factors impacting on early outcome (p > 0.05). However, TB7/TB0 ratio of <0.8 was an independent factor for good outcome (Odds ratio = 3.0, p = 0.006). Cox regression analysis demonstrated that 5-year survival rate was significantly correlated with TB7/TB0 ratio of <0.8 (HR = 0.46, 95 % CI 0.23–0.91, p = 0.025) and outcome at 6th month post-op (HR = 0.05, 95 % CI 0.01–0.15, p < 0.001). Conclusions: The >20 % decrease in serum TB at 7th day post-Kasai is a predictor for good outcome. BA patients with TB7/TB0 of <0.8 had 5-year survival with native livers significantly higher than those with the ratio of >0.8.